Evaluating Viking eco-cultural niche variability between the Medieval Climate Optimum and the Little Ice Age: a feasibility study - Antunes, Nicolas; Banks, William E.; D'Errico, Francesco (HAL CCSD, 2012)
International audience In the northern Atlantic, Norse agricultural and pastoral practices flourished from the 9th to the 13th century, after which Viking occupation of these regions abruptly declined and eventually disappeared towards the beginning of the 15th century. In this study, in order to evaluate the possible role of climatic variability on Viking settlement of these regions, we used the Genetic Algorithm for Rule-Set Prediction (GARP) to reconstruct the Viking eco-cultural niches during the end of the Medieval Warm Period (MWP) and the beginning of the Little Ice Age (LIA).These reconstructions demonstrate that the application of ECNM to this time period and Viking settlement dynamics is both feasible and relevant. Furthermore, preliminary results suggest that climate and environmental change played prominent roles in the abandonment of Greenland by Viking populations and are consistent with available historical accounts. Our results encourage us pursue further analyses with the use of more precise paleoclimatic and archaeological data in order to better understand the role of environmental change in the disappearance of Viking culture from regions of the northern Atlantic.